Pulmonary Cryptococcosis Diagnosed by Metagenomic Next-Generation Sequencing in a Young Patient With Normal Immune Function: A Case Report - Zhang, Yingyu; Wang, Weiliang; Zhang, Yingxuan; Zhai, Sina; Xia, Han; Zhang, Xilin (Frontiers in Public Health, 2022)
Background: Pulmonary cryptococcosis (PC) is a serious opportunistic fungal infection and usually occurs in immunocompromised patients. This disease is often difficult to diagnose in time due to its clinical manifestations and radiological feature similar to other pulmonary infections as well as the low sensitivity of conventional diagnostic methods. Cryptococcosis in immune competent patients is rare. Case presentation: Here we report a case of PC in an immune competent patient. Tuberculosis was suspected according to radiological feature due to positive T-lymphocyte spot test and pure protein derivative skin test. To further detect the pathogen, bronchoalveolar lavage fluid (BALF) was collected for metagenomic next-generation sequencing (mNGS). Cryptococcus neoformans (one specific read) was identified by mNGS, indicating PC of this patient. The following BALF culture and cryptococcal antigen lateral flow assay (CrAg-LFA) test also showed Cryptococcus infection, confirming the mNGS detection. Voriconazole (0.4g daily) was given orally according to the subsequent susceptibility results. After seven months of treatment, the patient’s condition improved. Conclusion: mNGS is a better diagnostic tool to help clinicians distinguish pulmonary cryptococcosis from other atypical pulmonary infections.